The Evolutionarily Conserved Protein PHOTOSYNTHESIS AFFECTED MUTANT71 Is Required for Efficient Manganese Uptake at the Thylakoid Membrane in Arabidopsis. Issue 4 (28th March 2016) - Schneider, Anja; Steinberger, Iris; Herdean, Andrei; Gandini, Chiara; Eisenhut, Marion; Kurz, Samantha; Morper, Anna; Hoecker, Natalie; Rühle, Thilo; Labs, Mathias; Flügge, Ulf-Ingo; Geimer, Stefan; et al.
Abstract : Analysis of an Arabidopsis mutant with a defect in photosystem II reveals that the integral thylakoid membrane protein PAM71 is involved in manganese and calcium homeostasis in the chloroplast. Abstract: In plants, algae, and cyanobacteria, photosystem II (PSII) catalyzes the light-driven oxidation of water. The oxygen-evolving complex of PSII is a Mn4 CaO5 cluster embedded in a well-defined protein environment in the thylakoid membrane. However, transport of manganese and calcium into the thylakoid lumen remains poorly understood. Here, we show that Arabidopsis thaliana PHOTOSYNTHESIS AFFECTED MUTANT71 (PAM71) is an integral thylakoid membrane protein involved in Mn 2+ and Ca 2+ homeostasis in chloroplasts. This protein is required for normal operation of the oxygen-evolving complex (as evidenced by oxygen evolution rates) and for manganese incorporation. Manganese binding to PSII was severely reduced in pam71 thylakoids, particularly in PSII supercomplexes. In cation partitioning assays with intact chloroplasts, Mn 2+ and Ca 2+ ions were differently sequestered in pam71, with Ca 2+ enriched in pam71 thylakoids relative to the wild type. The changes in Ca 2+ homeostasis were accompanied by an increased contribution of the transmembrane electrical potential to the proton motive force across the thylakoid membrane. PSII activity in pam71 plants and the corresponding Chlamydomonas reinhardtii mutant cgld1 was restored by supplementation with Mn 2+, but not Ca 2+ . Furthermore, PAM71 suppressed the Mn 2+ -sensitive phenotype of the yeast mutant Δpmr1 . Therefore, PAM71 presumably functions in Mn 2+ uptake into thylakoids to ensure optimal PSII performance.